Adenoviral L4 33K forms ring-like oligomers and stimulates ATPase activity of IVa2: implications in viral genome packaging - Ahi, Yadvinder S.; Vemula, Sai V.; Hassan, Ahmed O.; Costakes, Greg; Stauffacher, Cynthia; Mittal, Suresh K. (Frontiers in Microbiology, 2015)
The mechanism of genome packaging in adenoviruses (AdVs) is presumed to be similar to that of dsDNA viruses including herpesviruses and dsDNA phages. First, the empty capsids are assembled after which the viral genome is pushed through a unique vertex by a motor which consists of three minimal components: an ATPase, a small terminase and a portal. Various components of this motor exist as ring-like structures forming a central channel through which the DNA travels during packaging. In AdV, the IVa2 protein is believed to function as a packaging ATPase, however, the equivalents of the small terminase and the portal have not been identified in AdVs. IVa2 interacts with another viral protein late region 4 (L4) 33K which is important for genome packaging. Both IVa2 and 33K are expressed at high levels during the late stage of virus infection. The oligomeric state of IVa2 and 33K was analyzed in virus-infected cells, IVa2 and 33K transfected cells, AdV particles, or as recombinant purified proteins. Electron microscopy of the purified proteins showed ring-like oligomers for both proteins which is consistent with their putative roles as a part of the packaging motor. We found that the ATPase activity of IVa2 is stimulated in the presence of 33K and the AdV genome. Our results suggest that the 33K functions analogous to the small terminase proteins and so will be part of the packaging motor complex.